A method for estimating elbow varus torque using only a baseball with an embedded sensor - Shibata, S.; Mimura, K.; Shimana, T.; Maeda, A.; Fujii, M.; Suzuki, C.; Kageyama, M. (ISBS Proceedings Archive (Michigan), 2022)
Currently, to measure the elbow varus torque during baseball pitching, it is necessary to attach markers and sensors to the body. The purpose of this study is to develop the method for estimating elbow varus torque by only a baseball with an embedded sensor, and examine the accuracy. Eight baseball pitchers threw a four-seam fastball with maximum effort. The varus torque was estimated using one-link-segment model by an accelerometer and gyro sensor placed in the baseball. The Intraclass Correlation Coefficients between the maximum values of the varus torque calculated by the proposed method and the values calculated by the motion capture system was high (ICC(3,1) = 0.73).This result indicates that proof of concept by one-link model is success and warrants future research to potentially develop a system with greater accuracy.